2018
DOI: 10.1002/ajpa.23483
|View full text |Cite
|
Sign up to set email alerts
|

A time to be born: Variation in the hour of birth in a rural population of Northern Argentina

Abstract: This pattern may be associated with the circadian rhythms of hormone release, particularly melatonin, on a proximate level. At the ultimate level, giving birth in the early hours of the morning may have been selected to time births when the mother could benefit from the predator protection and support provided by her social group as well as increased mother-infant bonding from a more peaceful environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In some cases, research published in 2018 supported findings previously only demonstrated in Western settings, providing additional evidence of universal traits. Births at a rural Argentinian hospital, in which medical interventions were minimal, were shown to peak in the early morning hours—similar to patterns seen historically in the United States—providing additional support for the hypothesis that early morning births were evolutionary favored (Chaney, Goetz, and Valeggia ). Consistent with existing experimental data from Western, educated, industrial, rich, and democratic (WEIRD) populations, field experiments carried out with sixteen globally dispersed subsistence‐scale populations provided further evidence that pride is a universal human attribute that functions to help motivate cooperative behavior (Sznycer et al.…”
Section: Contextual Variation In Biology and Behaviorsupporting
confidence: 58%
“…In some cases, research published in 2018 supported findings previously only demonstrated in Western settings, providing additional evidence of universal traits. Births at a rural Argentinian hospital, in which medical interventions were minimal, were shown to peak in the early morning hours—similar to patterns seen historically in the United States—providing additional support for the hypothesis that early morning births were evolutionary favored (Chaney, Goetz, and Valeggia ). Consistent with existing experimental data from Western, educated, industrial, rich, and democratic (WEIRD) populations, field experiments carried out with sixteen globally dispersed subsistence‐scale populations provided further evidence that pride is a universal human attribute that functions to help motivate cooperative behavior (Sznycer et al.…”
Section: Contextual Variation In Biology and Behaviorsupporting
confidence: 58%
“…Recently, MacFarlane and colleagues, based on data from England and Wales [ 7 , 21 ], found wide variations based on day of the week, birth setting, and medical interventions. Most prior studies have been based on data from single hospitals, regional collaborations, national hospitals or vital statistics data from a single country [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, time of day has been shown to influence birth events in other animals, such as Lipizzaner mares ( Equus ferus caballus ) on stud farms delivering over 90% of their foals between 18:00–06:00 h, and 63% between 21:00–03:00 h (Heidler et al, 2004), when human disturbance would be minimal. There is also an observed clustering of noninduced vaginal births of human infants between 01:00–07:00 h. This was deemed to be because of minimal disturbance and mother–infant bonding opportunities (Chaney et al, 2018).…”
Section: Introductionmentioning
confidence: 99%